INFERTILITY IN FEMALES IN CONTEXT OF ANTISPERM ANTIBODIES IN PELVIC INFLAMMATORY DISEASE (PID) AND POLYCYSTIC OVARIAN SYNDROME (PCOS) - K. ROY GEORGE,; N. A MALINI, (The Bioscan, 2012)
The present study has been designed to evaluate the various causes of female infertility prevailing among Central Travancore women and to relate the incidence of antisperm antibodies (ASA) with altered hormonal profile in these infertile cases. A total of 500 women (21 – 35) who were subjected to infertility treatment at various infertility clinics in Kottayam, Pathanamthitta and Alappuzha districts and hundred normal healthy women (20 – 35) with proven fertility at the luteal phase were taken as subjects. The data were collected from hospital records as well as using an investigator administered questionnaire. The clinical studies revealed that polycystic ovary syndrome (PCOS) is the major cause of female infertility (33.6 %). High incidence of ASA was observed in various infertile cases. The ASAs were found in 13.8 % of the total infertile cases. Pelvic inflammatory disease (PID) constituted the maximum of cases (32%) followed by unidentified cases (25.71 %), polycystic ovary syndrome (PCOS) (22.6%) and other infertile cases (5.14%). The control group showed 5% incidence of ASAs. Markedly higher incidence of ASA in cases of PCOS as well as in PID, the increased insulin resistance with higher level of blood glucose, points to an enhanced production of ASA due to the insulin mediated endocrine disruption. This study points to an insulin dependent endocrine-immune disruption in cases of female infertility.